Comparison of Fluid Analysis and Cytologic Findings of Cerebrospinal Fluid Between Three Collection Sites in Adult Equids With Neurological Disease - Young, Kimberly A. S.; Hepworth-Warren, Kate L.; Dembek, Katarzyna A. (Frontiers in Veterinary Science, 2022)
Cerebrospinal fluid (CSF) is routinely collected from three sites in the horse, the atlanto-occipital (AO), lumbosacral (LS) and atlantoaxial (AA) space. A comparison between fluid analysis parameters (total protein, white blood cell (WBC) count, red blood cell (RBC) count, morphologic analysis) from samples obtained at each of the three sites has not previously been performed. A retrospective analysis was performed to evaluate the differences in fluid analysis of CSF between the AO, LS, and AA sites in equids presented to a referral service for evaluation of suspected neurologic disease. 113 equids aged ≥1 year that underwent CSF collection between 2008-2020 were included. White blood cell count, red blood cell count, total protein (TP), and morphologic evaluation between CSF samples obtained from the three sites were compared. When comparing all samples, LS centesis was associated with increased RBC compared to other sites (P <0.05); total protein was lower in the AA group than the LS (P <0.05). Within a subset of cytologically normal samples, RBC concentration was highest in LS samples (P <0.01); TP was higher in LS samples compared to AA samples (P<0.05) and WBC concentration was higher (P <0.01) in AA and LS groups compared to the AO. In cytologically abnormal samples, there were no significant differences between sites in any parameter. Abnormal cytology was correlated with non-survival (P=0.0002). Non-survival was associated with increased WBC (P <0.01). The receiver operating characteristic curve (ROC) for WBC had an area under the curve of 0.67 (95% CI, 0.55-0.79) and indicated that a cutoff value of 24 cells/µL maximized specificity (72%) and sensitivity (54%) to predict non-survival in all horses. Positive predictive value was 45%; negative predictive value was 78%. Blood contamination was higher in samples from the LS site. This has clinical implications due to the importance of comparative diagnostics and its potential impact on cytologic evaluation. There were minimal differences in multiple other parameters between sites, which are likely clinically insignificant.